BDNF Polymorphism: A Review of Its Diagnostic and Clinical Relevance in Neurodegenerative Disorders - Shen, Ting; You, Yuyi; Joseph, Chitra; Mirzaei, Mehdi; Klistorner, Alexander; Graham, Stuart L.; Gupta, Vivek (Aging and disease, 2018)
Brain-derived neurotrophic factor (BDNF) has a unique role in the neuronal development, differentiation, and survival in the developing and adult nervous system. A common single-nucleotide polymorphism in the pro-region of the human BDNF gene, resulting in a valine to methionine substitution (Val66Met), has been associated with the susceptibility, incidence, and clinical features of several neurodegenerative disorders. Much research has been dedicated to evaluating the effects of polymorphism in the past decade, and functional effects of this genetic variation. A better understanding of how this naturally occurring polymorphism associates with or influences physiology, anatomy, and cognition in both healthy and diseased adults in neurodegenerative conditions will help understand neurochemical mechanisms and definable clinical outcomes in humans. Here we review the role and relevance of the BDNF Val66Met polymorphism in neurodegenerative diseases, with particular emphasis on glaucoma, multiple sclerosis (MS), Alzheimer's disease (AD) and Parkinson's disease (PD). Several controversies and unresolved issues, including small effect sizes, possible ethnicity, gender, and age effects of the BDNF Val66Met are also discussed with respect to future research.